2018
DOI: 10.3390/nu10111752
|View full text |Cite
|
Sign up to set email alerts
|

Response to “Are There Non-Responders to the Ergogenic 3 Effects of Caffeine Ingestion on Exercise Performance?”

Abstract: In response to “Letter: are there non-responders to the ergogenic effects of caffeine ingestion on exercise performance” by Grgic [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Both emphasized a current clinical interest limited to CYP1A2 and ADORA2A variations, suggesting opportunities to expand this research to more recent loci identified by GWAS. Despite the advancements in integrating genetics into clinical trials of caffeine, such designs remain susceptible to limitations [ 9 , 10 , 12 , 13 ]. Some of these limitations were further highlighted by Shabir et al [ 14 ] in their critical review on the impact of caffeine expectancies on sport, exercise, and cognitive performance.…”
mentioning
confidence: 99%
“…Both emphasized a current clinical interest limited to CYP1A2 and ADORA2A variations, suggesting opportunities to expand this research to more recent loci identified by GWAS. Despite the advancements in integrating genetics into clinical trials of caffeine, such designs remain susceptible to limitations [ 9 , 10 , 12 , 13 ]. Some of these limitations were further highlighted by Shabir et al [ 14 ] in their critical review on the impact of caffeine expectancies on sport, exercise, and cognitive performance.…”
mentioning
confidence: 99%
“…Understanding these expectations is critical to assess the risk of bias in clinical trials in sports science due to the ergogenic or ergolytic effects of placebo associated with the effects of caffeine. Literature shows how the placebo effect ( 33 , 34 ), either due to excess or lack of expectation about the effect of caffeine ( 12 , 14 , 35 , 36 ), can represent a possible risk of bias for the main findings of the research. For example, scores above the national average for factors may indicate a tendency to respond to caffeine supplementation.…”
Section: Discussionmentioning
confidence: 99%